2017
DOI: 10.1007/s11745-017-4262-1
|View full text |Cite
|
Sign up to set email alerts
|

2‐Methoxylated FA Display Unusual Antibacterial Activity Towards Clinical Isolates of Methicillin‐Resistant Staphylococcus aureus (CIMRSA) and Escherichia coli

Abstract: The naturally occurring (6Z)-(±)-2-methoxy-6-hexadecenoic acid (1) and (6Z)-(±)-2-methoxy-6-octadecenoic acid (2) were synthesized in 7–8 steps with 38% and 13% overall yields, respectively, by using an acetylide coupling approach, which made it possible to obtain a 100% cis-stereochemistry for the double bonds. In a similar fashion, the acetylenic analogs (±)-2-methoxy-6-hexadecynoic acid (3) and (±)-2-methoxy-6-octadecynoic acid (4) were also synthesized in 6–7 steps with 48% and 16% overall yields, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Once the bacterial characterization tests were performed, microdilution susceptibility tests were carried out as described before (Carballeira et al, ; Sanabria‐Rios et al, , ). Table shows the antibacterial activity of aFA against MRSA ATCC 43300 and three CIMRSA strains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Once the bacterial characterization tests were performed, microdilution susceptibility tests were carried out as described before (Carballeira et al, ; Sanabria‐Rios et al, , ). Table shows the antibacterial activity of aFA against MRSA ATCC 43300 and three CIMRSA strains.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the potential of unsaturated fatty acids as antibacterial agents (Carballeira et al, 1998(Carballeira et al, , 2002(Carballeira et al, , 2006(Carballeira et al, , 2017Konthikamee et al, 1982;Morbidoni et al, 2006;Sanabria-Rios et al, 2014. For example, in a study performed by Carballeira et al, 1998, the (Z)-2-methoxy-5-hexadecenoic and (Z)-2-methoxy-6-hexadecenoic acids were biologically active against S. aureus and Streptococcus faecalis at minimal inhibitory concentrations (MIC) of 0.35 μM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of FAs, oleic acid (a monounsaturated FA, C18:1n-9) possesses a potent activity against both spoilage and pathogenic bacteria (e.g., Staphylococcus aureus, E. coli, Helicobacter, Clostridium and Salmonella species etc.) [22][23][24]. More importantly, reports have shown that a higher content of oleic acid is associated with better flavor characteristics of meat [25], since it contributes significantly to the development of cooked meat aromas [26].…”
Section: Introductionmentioning
confidence: 99%